2010
DOI: 10.4314/ijbcs.v4i2.58125
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of serum ferritin levels after oral supplementation with ferrous sulphate and carbonyl iron in mild iron deficiency anemia in pregnancy

Abstract: Iron supplementation is almost universally recommended during pregnancy to correct or prevent iron deficiency. Iron status can be assessed prepartum by estimating blood hemoglobin concentration, serum iron, serum total iron binding capacity (TIBC) and serum ferritin. This study attempts to know the therapeutic efficacy of the drugs, ferrous sulphate and carbonyl iron, in improving the iron stores to meet the increased demand during pregnancy. A comparative study was done in two groups of 36 pregnant women each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Similar results were observed in the study conducted by N. Chandrika and KC Vasudha. [14] In our study about 90% of the patients in the Carbonyl iron group achieved the WHO target of 11 gm% as compared to the ferrous sulphate group where only 20% and the ferrous fumarate group where 35% of the patients were able to achieve the WHO target.…”
Section: Groupmentioning
confidence: 85%
“…Similar results were observed in the study conducted by N. Chandrika and KC Vasudha. [14] In our study about 90% of the patients in the Carbonyl iron group achieved the WHO target of 11 gm% as compared to the ferrous sulphate group where only 20% and the ferrous fumarate group where 35% of the patients were able to achieve the WHO target.…”
Section: Groupmentioning
confidence: 85%
“…Serum ferritin changes were significantly higher at weeks 3 to 5. Chandrika et al [24] analyzed mild iron deficiency anemia in pregnancy and concluded that change (mean difference) in Hb, serum ferritin, and serum iron in ferrous sulphate group significantly increased. Similar studies observed increases and decreases in iron parameters could be attributed to different patient groups, dose and therapy variations and follow-up timelines.…”
Section: Discussionmentioning
confidence: 99%
“…So, limitations of conventional iron salts have resulted in emergence of newer oral iron preparations like Carbonyl iron, Iron polymaltose complex, Ferrous ascorbate, Sodium feredetate and Ferrous bisglycinate. 5 A mild deficiency should not affect baby while pregnancy. But if mild iron deficiency anemia goes untreated and becomes more severe during pregnancy is linked to an increased risk of a baby being born with a low birth weight.…”
Section: Introductionmentioning
confidence: 99%